Morphological changes of river Bank Erosion and channel shifting assessment on Arial Khan River of Bangladesh using Landsat satellite time series images - Irteja Hasan; Joyjit Dey; Md. Mustafizur Rahman Munna; Afiadeal Preya; Tahrin Bhuiyan Nisanur; Munira Jaman Memy; Mst. Zihan Shazia Zeba (Progress in Disaster Science)
The continuous processes of erosion and deposition in rivers are intricately linked to changes in land use and land cover (LULC), reflecting dynamic landscape transformations. This study investigates the rate of riverbank erosion, channel shifting, and the impact of erosion on LULC dynamics along the Arial Khan River. Utilizing GIS and remote sensing techniques, we analyzed time-series satellite images from 1993 to 2024 within a 2 km buffer zone of the floodplain. Supervised classification methods were applied for LULC analysis, with results validated using confusion matrices to assess classification accuracy. ArcGIS 10.8 was employed to analyze channel centerline migration, while NDVI analysis assessed vegetation health. The study reveals that between 1993 and 2024, 5142.60 ha were lost to erosion, while deposition affected 4756.52 ha, with erosion surpassing deposition overall. The river shifted an average of 0.66 km during this period, with higher migration rates in Muladi Upazila compared to Babuganj Upazila. Settlement areas expanded significantly from 137.82 ha in 1993 to 2768.68 ha in 2024, while agricultural land declined substantially. These findings provide valuable insights for policymakers to address erosion severity in confluence zones and lay the groundwork for sustainable land management practices.